Predictors of Total Mortality and Echocardiographic Response for Cardiac Resynchronization Therapy: A Cohort Study - Gazzoni, Guilherme Ferreira; Fraga, Matheus Bom; Ferrari, Andres Di Leoni; Soliz, Pablo da Costa; Borges, Anibal Pires; Bartholomay, Eduardo; Kalil, Carlos Antonio Abunader; Giaretta, Vanessa; Rohde, Luis Eduardo Paim (Arquivos brasileiros de cardiologia, 2017)
Clinical studies demonstrate that up to 40% of patients do not respond to cardiac resynchronization therapy (CRT), thus, appropriate patient selection is critical to the success of CRT in heart failure. Evaluation of mortality predictors and response to CRT in the Brazilian scenario. Retrospective cohort study including patients submitted to CRT in a tertiary hospital in southern Brazil from 2008 to 2014. Survival was assessed through a database of the State Department of Health (RS). Predictors of echocardiographic response were evaluated using Poisson regression. Survival analysis was performed by Cox regression and Kaplan Meyer curves. A two-tailed p value less than 0.05 was considered statistically significant. A total of 170 patients with an average follow-up of 1011 ± 632 days were included. The total mortality was 30%. The independent predictors of mortality were age (hazard ratio [HR] of 1.05, p = 0.027), previous acute myocardial infarction (AMI) (HR of 2.17, p = 0.049) and chronic obstructive pulmonary disease (COPD) (HR of 3.13, p = 0.015). The percentage of biventricular stimulation at 6 months was identified as protective factor of mortality ([HR] 0.97, p = 0.048). The independent predictors associated with the echocardiographic response were absence of mitral insufficiency, presence of left bundle branch block and percentage of biventricular stimulation. Mortality in patients submitted to CRT in a tertiary hospital was independently associated with age, presence of COPD and previous AMI. The percentage of biventricular pacing evaluated 6 months after resynchronizer implantation was independently associated with improved survival and echocardiographic response.